Vascular Cognitive Impairment through the Looking Glass of Transcranial Magnetic Stimulation - Giuseppe Lanza; Placido Bramanti; Mariagiovanna Cantone; Manuela Pennisi; Giovanni Pennisi; Rita Bella (Behavioural Neurology, 2017)
In the last years, there has been a significant growth in the literature exploiting transcranial magnetic stimulation (TMS) with the aim at gaining further insights into the electrophysiological and neurochemical basis underlying vascular cognitive impairment (VCI). Overall, TMS points at enhanced brain cortical excitability and synaptic plasticity in VCI, especially in patients with overt dementia, and neurophysiological changes seem to correlate with disease process and progress. These findings have been interpreted as part of a glutamate-mediated compensatory effect in response to vascular lesions. Although a single TMS parameter owns low specificity, a panel of measures can support the VCI diagnosis, predict progression, and possibly identify early markers of “brain at risk” for future dementia, thus making VCI a potentially preventable cause of both vascular and degenerative dementia in late life. Moreover, TMS can be also exploited to select and evaluate the responders to specific drugs, as well as to become an innovative rehabilitative tool in the attempt to restore impaired neural plasticity. The present review provides a perspective of the different TMS techniques by further understanding the cortical electrophysiology and the role of distinctive neurotransmission pathways and networks involved in the pathogenesis and pathophysiology of VCI and its subtypes.